Verotoxigenic Escherichia coli (VTEC) isolated from cow milk - Suwito, Widodo (Indonesian Animal Sciences Society, 2009)
Verotoxigenic Escherichia coli (VTEC) strains are responsible for serious human illnesses. These strains are commonly found in milk. The aim of this study was to determine the occurrence of verotoxigenic E. coli in milk. A total of 351 milk samples, were collected from dairy farms in Bogor, Sukabumi and Cianjur. These samples were analyzed for VTEC using biochemical, serological and vero cell cytotoxicity assays. VTEC O157:H7 isolates were found in milk collected from dairy herds in Bogor and Sukabumi at rates 0.47% of 214 samples, 1.10% of 91 samples respectively, and none in Cianjur. Hemolytic E. coli isolates were found in 0.94% of 214 milk samples from Bogor, 2.2% of 91 milk samples from Sukabumi and none from Cianjur. From E. coli isolates, 53 isolates (67.95%) were verotoxigenic, consisted of: two E. coli O157:H7 isolates and 51 non O157:H7 isolates.Therefore this study showed the occurrence of VTEC in milk samples from dairy farms in Bogor, Sukabumi and Cianjur. Key words: Milk, E. coli (VTEC) O157:H7, Verotoxigenic